Buku Percakapan Bahasa Arab Dengan Pendekatan Kontekstual: Pengembangan Buku Percakapan Bahasa Arab - Khairil Anwar (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2020)
This research aim to (1) production of conversation book withcontextual approach prespective to developing of speech Skill in Baitul Jannah Junior High School Lampung (2) survey the effectiveness of using conversation book with contextual approach prespective in Baitul Jannah Junior High School Lampung. The methodology that is used in this research is research and development, while the research that used to produce and examine its effectiveness. The step production of conversation book contextual approach perspective to cultivate speech skill in Baitul Jannah Junior High School Lampung is used step by Borg and Ghall and the trial design which is used in one group pretest posttest to determine the effectiveness of trial in this Arabic learning. While the sample was grade 7 “Tahfidz” whit the amount of 30 students. The findings showed are : (1) Produce the conversation book with a contextual approachto cultivate speech skill in Baitul Jannah Junior High School Lampung and characteristic of this book is the theme, vocabulary, conversation and picture related of the culture and activity in Baitul Jannah Junior High School (2)Conversation book is generated by using the contextual approach is effective in field trials research. It is known when researchers compare the value of pretest posttest, so that the value of sig.(2tailed)is0,00 of >0,05، and that mean Horejected and Ha accepted and the conversation book whith a contextual approach is effective.